Dasatinib inhibits coated-platelet generation in patients with chronic myeloid leukemia. (3rd October 2019) - Mezei, Gabriella; Debreceni, Ildiko Beke; Kerenyi, Adrienne; Remenyi, Gyula; Szasz, Robert; Illes, Arpad; Kappelmayer, Janos; Batar, Peter
Abstract: Since the introduction of tyrosine kinase inhibitors, the overall survival of patients with chronic myeloid leukemia has markedly improved. However long term use of these drugs results in various adverse events. Treatment with second generation dasatinib is often complicated by hemorrhagic events. Previous lumi-aggregometry studies have shown impaired platelet function in patients on dasatinib therapy. Dual agonist activated platelets (coated-platelets) are also sensitive indicators of platelet function. We hypothesized that dual activation with convulxin and thrombin of platelets in a flow cytometric assay could be a more sensitive method for detecting platelet dysfunction as compared to single agonist studies used in lumi-aggregometer. Platelets of healthy volunteers incubated with dasatinib as well as platelets from patients on dasatinib therapy were investigated. Low therapeutic plasma level dasatinib concentrations at which a considerable reduction in coated-platelet generation was observed in vitro, did not cause detectable change in platelet aggregation response. Coated-platelet assay and lumi-aggregometry were also investigated at 0, 1 and 4 hours after drug administration in dasatinib treated CML patients. Significant decrease was observed at 1 hour in maximal aggregation by collagen. Although the aggregation curves became normalized by 4 hours, coated-platelet generation was still inhibited in dasatinib treated patients. Nilotinib, another second generation tyrosine kinase inhibitor, had no effect on aggregation and on coated-platelet formation neither in vitro nor in ex vivo samples. At therapeutic plasma levels coated-platelet assay is more sensitive than lumi-aggregometry studies for the demonstration of the inhibitory effect of dasatinib on platelet function.